Quantitative Determination of an Antiviral Drug Ganciclovir by Redox-based Spectrophotometric Method - Naraparaju Swathi; Barla Karuna Devi; Anumolu Durga Pani Kumar (Pharmaceutical Research - Recent Advances and Trends Vol. 1, 2024)
Ganciclovir functions as an antiviral medication crucial for averting cytomegalovirus disease among recipients of bone marrow and solid organ transplants. Furthermore, it plays a pivotal role in managing individuals with compromised immune systems by combatting viral infections effectively. This study aims to develop and validate a simple, rapid and sensitive redox-based spectrophotometric method for the quantification of Ganciclovir in pure and pharmaceutical dosage forms. The development process involved utilizing 0.1 M HCl as the solvent along with a combination of ferric chloride and 1,10-phenanthroline as the chromogenic reagent. After development, the method underwent optimization across various conditions to ensure its efficacy, followed by rigorous statistical validation. Based on the optimization studies, it was determined that the optimal composition for the method included a mixture containing 0.3% w/v of ferric chloride and 0.5% w/v of 1,10-phenanthroline, with a drug-to-reagent mole ratio of 0.5:0.5. When measured at 510.0 nm, the method exhibited linearity within the concentration range of 5.0-30.0 \(μ)/mL for Ganciclovir. Demonstrating its sensitivity, the method showcased a low limit of detection and quantification values, recorded at 0.30 and 0.90 \(μ)/mL, respectively. The validation parameters of the method were found to align with the standards outlined by the ICH guidelines. With a % assay value of 99.2, the method demonstrated its suitability for pharmaceutical formulation analysis. The simplicity of the developed method renders it suitable for application in quality control testing of Ganciclovir within formulations.